Do matizado do copo ao matizado da escrita : o pacto de leitura em Deleite do estrangeiro em tudo o que é espantoso e maravilhoso - Oliveira, Maria Aparecida de (2017)
Deleite do Estrangeiro em tudo o que é espantoso e maravilhoso is a story about the trip of Abduurrahman Bin Abdullah al-Baghdádi, an Iraqi muslim imam, who was in Brazil in the 19th century and registered three years of his period in the country where he collaborated with communities which were brought from Africa and slaved. The record in the form of rihla, a literary genre of the tradition of Arab-Muslim travels, is the manuscript translated into Portuguese, in which the Muslim leader, in addition to reporting the experience with the Muslim communities, also describes some aspects about animals, plants and habits in the 19th century in the places he was. The narrative construction of al-Baghdádi's rihla, which shows the fictionalization of facts, starting with Arab-Islamic traditional and literary imagery such as “Sinbad The Sailor” stories, is what constitutes the main object of this analysis, which sought to investigate it under the notion of a "reading pact" as fictionalization is organized around meanings shared by the Arab-Muslim community. In this way, the analysis is based on a reading about the frontier places, problematized by Homi Bhabha (2003), taking into account those constructions that take place in the narrative in the experiences of the Muslims, as well as in the process of resignification from the learning of the Sunni principles, guided by al-Baghdádi.